Smart Villages in EU Policy: How to Match Innovativeness and Pragmatism? - Oskar Wolski (Wieś i Rolnictwo)
Smart Villages is an approach to rural development which has been under discussion in the EU as one of the subthemes that the ENRD is working on. For this reason, the Thematic Group (TG) on Smart Villages was launched in 2017. Since then it has been contributing to the definition of smart villages, discussing the changes in rural development policy and opportunities for providing support for smart villages, exchanging experience and best practices in smart rural development, and serving as a forum for dialogue between various rural stakeholders. This paper outlines the discussion held during the selected meetings of the TG and briefly indicates the academic background of the approach discussed. Its aim was to present Smart Villages in terms of EU policy. Hence, the paper presents the genesis of the EU debate, highlights some of the dilemmas of the definition of smart villages, indicates the role of the territorial governments and the EU in creating the conditions for implementing the approach, and shows the selected examples of smart rural development. Smart Villages is an alternative way of thinking about the quality of rural life, and it seems to respond to the way the EU policy is evolving. However, it calls for better tailored tools and instruments, which applies both to EU policies and national/regional sources. It also calls for regional and local governments to play their role in the process.